The Effect of Population Density and Intercropping with Tomato on the Growth and Yield of Winged Bean (Psophocarpus tetragonolobus) - Maure, Gerson Hans; Chozin, Muhammad Achmad; Santosa, Edi (Journal of Tropical Crop Science, 2019)
Winged bean (Fabaceae) is a tropical crop that has high nutrient content, and almost all parts of the plant are edible. The research aimed to evaluate the growth and production of winged bean in an intercropping system with tomato. The study was conducted at the Cikabayan Experimental Field of Bogor Agricultural University, Bogor, Indonesia, in a randomized block design with three replications during the rainy season of December 2017 to June 2018. Winged beans were planted in high and low population densities and intercropped with three tomato genotypes, “Tora”, F70030081-12-16-3 and “Apel Belgia”. Monoculture winged bean was assigned as control. Tomatoes were planted between the rows of the winged beans in the intercropping treatment. The results showed that the growth of winged bean in monoculture and intercropping systems was not significantly different. The photosynthetic activity of winged bean at three to five weeks after planting remained high, indicating that the vegetative growth was optimal in both systems. Intercropping increased the winged bean number of pods per plant by 12.66-19.52% compared to monoculture, irrespective of population density. Therefore, winged bean could be considered as suitable to grow in intercropping systems.